Single-cell transcriptome profiling of the human endometrium of patients with intrauterine adhesions - Ping Li; Yu Jian; Xinyi Liu; Li Pan; Zhihui Tan; Nianchun Shan (Scientific Reports)
Abstract Intrauterine adhesions (IUAs) are a complex condition that frequently results in menstrual disturbances, infertility, and obstetric complications. Unfortunately, the underlying pathophysiology of IUAs remains poorly understood, and current treatments often exhibit limited efficacy. We performed the single-cell RNA-sequencing (scRNA-Seq) comparison of 5 endometrial tissues, including patients with confirmed intrauterine adhesions and healthy controls(HCs). We profiled the transcriptomes of 55,308 primary human endometrial cells isolated from healthy controls and intrauterine adhesions patients at single-cell resolution. Compared with those in HCs, the number of fibroblasts derived from IUAs significantly decreased. Further analysis found that fibroblasts subcluster 3 were enriched in the IUAs, whereas opposite in HCs. GO enrichment analysis revealed that specific genes of fibroblasts subcluster 3 were markedly involved in the positive regulation of embryonic placenta development, the response to reactive oxygen species and female pregnancy, and the positive regulation of the mitotic DNA damage checkpoint and DNA damage response. In addition, the proportion of proliferating endothelial cells was significantly lower in IUAs. GO enrichment analysis revealed that the specific genes were markedly involved in the positive regulation of cell cycle arrest, the cellular response to interferon − gamma and the negative regulation of the mitotic cell cycle. According to the number of intercellular receptor–ligand pairs, we identified endothelial cells as the core cell population. Our study provides deeper insights into the endometrial microenvironment disorders that are potentially applicable to improving therapeutics for IUAs.